The Effect of Zinc Doped Bismuth Ferrite on Changes in Structural and Microwave Absorption Properties through the Sol Gel Synthesis Method: Microwave Absorption Properties on Zinc doped Bismuth Ferrite Nanocrystalline by Sol-gel Method - Wira Sukarsa, Suharno; Soegiyono, Bambang; Budiawanti, Sri (International Journal of Integrated Engineering, 2022)
The zinc (Zn) doped bismuth ferrite (BiFeO3) have been successfully synthesized through the sol-gel autocombustion method as a microwave absorbent material through a composite process with silicone rubber. The characterizations of zinc doped bismuth ferrite nanoparticles was done using the X-Ray Diffraction (XRD), the Fourier Transform Infrared (FTIR), the Vibration Sample Magnetometer (VSM), and the Vector Network Analyzer (VNA). Through the XRD test, the nanoparticle BiFe1-xZnxO3 (x = 0, 0.06, 012) have a crystal structure of rhombohedral R3c. Through the FTIR test, it were observed that the area of ​​wave number 491 - 569 cm-1 were used as an absorber for BiFeO3, while the one in zinc doped BiFeO3 were observed to be 489 - 636 cm-1. The VSM test shows that the BiFe1-xZnxO3 nanoparticles (x = 0, 0.06, 012) have ferromagnetic properties and potentially change to paramagnetic properties with the addition of zinc doping. The VNA test were obtained, bismuth ferrite without doping has a reflection loss (RL) of -25.79 dB with a narrower frequency range and bismuth ferrite with zinc doping (%wt x = 0.12) has a RL of -30.02 dB with a wider frequency range so that zinc doped BiFeO3 potentially to be a good absorbent material.